211k views
4 votes
If h(x) = (fog) (x) and h(x) = 4 square root x+7, find g(x) if f(x) = 4 square root x+ 1

User Axel Meier
by
5.9k points

1 Answer

3 votes

Answer:


g(x)=x+6 is the answer

given


h(x)=4√(x+7) and
f(x)=4√(x+1).

Explanation:


h(x)=(f \circ g)(x)


h(x)=f(g(x))

Inputting the given function for h(x) into the above:


4√(x+7)=f(g(x))

Now we are plugging in g(x) for x in the expression for f which is
4√(x+1) which gives us
4√(g(x)+1):


4√(x+7)=4√(g(x)+1)

We want to solve this for g(x).

If you don't like the looks of g(x) (if you think it is too daunting to look at), replace it with u and solve for u.


4√(x+7)=4√(u+1)

Divide both sides by 4:


√(x+7)=√(u+1)

Square both sides:


x+7=u+1

Subtract 1 on both sides:


x+7-1=u

Simplify left hand side:


x+6=u


u=x+6

Remember u was g(x) so you just found g(x) so congratulations.


g(x)=x+6.

Let's check it:


(f \circ g)(x)


f(g(x))


f(x+6) I replace g(x) with x+6 since g(x)=x+6.


4√((x+6)+1) I replace x in f with (x+6).


4√(x+6+1)


4√(x+7)


h(x)

The check is done. We have that
(f \circ g)(x)=h(x).

User Qstebom
by
6.9k points